Triblock copolyesters derived from lactic acid and glucose: Synthesis, nanoparticle formation and simulation. (July 2017) - Zakharova, Elena; León, Salvador; de Ilarduya, Antxon Martínez; Muñoz-Guerra, Sebastián
Graphical abstract: Highlights: Amphiphilic triblock copolyesters made from glucose and lactic acid were synthesized. Hydroxyl ended poly(glucitylene succinate) was the initiator for the ROP of lactide. Bulk copolyesters are amorphous and have an only T g indicating no phase segregation. Nanoparticles made of copolyesters were sensitive to light changes in temperature. Nanoparticles are biphasic with separated hydrophobic and hydrophilic domains. Abstract: ABA triblock copolyesters were synthesized by ring-opening polymerization (ROP) ofl -lactide in solution initiated by a telechelicd -glucose-based polyester macroinitiator. The macroinitiator with a number-average molecular weight about 2500 g mol −1 was synthesized by non-stoichiometric polycondensation in the melt of 2, 4:3, 5-di- O -methylene-d -glucitol and dimethyl succinate. Two triblock copolyesters of M n ranging between ∼6000 and ∼9000 g mol −1, and differing in the length of the polylactide blocks were prepared. These copolyesters started to decompose when heated at ∼220 °C and degraded slowly upon aqueous incubation under physiological conditions. They did not display any perceivable crystallinity and showed a single glass transition temperature ( T g ) around 60 °C with the higher value corresponding to the larger content in glucitol units. The copolyesters were able to form nanoparticles with average diameters of ∼100–130 nm and satisfactory dispersity. The effect of the block lengths on size, ζ -potential values and physical stability of the nanoparticles was evaluated. A molecular dynamics simulation study allowed modelling the two-phase structure of the nanoparticles and evidenced the preference of the glucose-based block to be peripherally located.